2021
DOI: 10.3390/nano11040897
|View full text |Cite
|
Sign up to set email alerts
|

Group Theory Analysis to Study Phase Transitions of Quasi-2D Sr3Hf2O7

Abstract: We present an ab-initio study performed in the framework of density functional theory, group-subgroup symmetry analysis and lattice dynamics, to probe the octahedral distortions, which occur during the structural phase transitions of the quasi-2D layered perovskite Sr3Hf2O7 compound. Such a system is characterized by a high-temperature I4/mmm centrosymmetric structure and a ground-state Cmc21 ferroelectric phase. We have probed potential candidate polymorphs that may form the I4/mmm → Cmc21 transition pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…14 In addition to HIF, the octahedral reorientations in layered perovskites are of continuing interest because these effects also trigger many interesting electronic properties, such as high-T c superconductivity, colossal magnetoresistance, metal-insulator transitions, and magnetic ordering. 15 Recent theoretical works from Liu et al 16 and da Silva et al 17 confirmed that Sr 3 Hf 2 O 7 (SHO), a n = 2 quasi-2D RP layered perovskite system, with a ferroelectric ground state Cmc2 1 (S.G. n. 36), is similar to the previously reported HIF systems, such as Ca 2 Mn 3 O 7 and Ca 2 Ti 3 O 7 , in ref 15. SHO is also characterized by a high-temperature I4/mmm (S.G. n. 139) centrosymmetric paraelectric structure.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…14 In addition to HIF, the octahedral reorientations in layered perovskites are of continuing interest because these effects also trigger many interesting electronic properties, such as high-T c superconductivity, colossal magnetoresistance, metal-insulator transitions, and magnetic ordering. 15 Recent theoretical works from Liu et al 16 and da Silva et al 17 confirmed that Sr 3 Hf 2 O 7 (SHO), a n = 2 quasi-2D RP layered perovskite system, with a ferroelectric ground state Cmc2 1 (S.G. n. 36), is similar to the previously reported HIF systems, such as Ca 2 Mn 3 O 7 and Ca 2 Ti 3 O 7 , in ref 15. SHO is also characterized by a high-temperature I4/mmm (S.G. n. 139) centrosymmetric paraelectric structure.…”
Section: Introductionsupporting
confidence: 67%
“…Such a transition can occur by applying an external perturbation, such as pressure, in order to induce the condensation of the X 1 − zone boundary mode from the centrosymmetric system. 17 We show in Figure 1 the four structural phases we have studied in this investigation. They are:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations